Analisis Kekuatan Tarik Komposit Polimer Epoksi Dengan Tepung Cangkang Telur Sebagai Filler Ditinjau Dari Variasi Waktu Pengangkatan Spesimen Menggunakan Metode Hand Lay-Up - Adnan Zaidan ‘Ibadurohman (CV. SINAR HOWUHOWU, 2026)
Chicken eggshell waste is an organic waste whose quantity continues to increase due to the high consumption of eggs by the community. Eggshells contain a high amount of calcium carbonate (CaCO₃), making them a potential filler material for polymer composites. One of the factors that is presumed to affect the mechanical properties of composites is the specimen removal time (demoulding time), as it is related to the curing process of epoxy resin. This study aims to analyze the effect of demoulding time variation on the tensile strength of epoxy polymer composites reinforced with chicken eggshell powder filler fabricated using the hand lay-up method. This study employed an experimental method with five demoulding time variations, namely 6, 12, 24, 36, and 48 hours. The materials consisted of epoxy resin, hardener, and 100-mesh chicken eggshell powder with a filler fraction of 10%. Each variation consisted of three specimens, resulting in a total of 15 specimens. Tensile testing was conducted in accordance with ASTM D638. The test data were analyzed using One-Way Analysis of Variance (ANOVA) and supported by macro photo analysis of the fracture surfaces. The results showed that the average tensile strengths for the 6, 12, 24, 36, and 48-hour demoulding time variations were 12.68 MPa, 28.80 MPa, 24.29 MPa, 23.35 MPa, and 24.91 MPa, respectively. The 12-hour variation produced the highest tensile strength, while the 6-hour variation produced the lowest value. The One-Way ANOVA yielded an F-value of 4.03, which was greater than the F-table value of 3.48 at a 5% significance level, indicating that demoulding time had a significant effect on the tensile strength of the composite. Macro photo analysis revealed that the 12-hour specimens exhibited a more homogeneous fracture surface with fewer voids than the 6-hour specimens, supporting the improvement in tensile strength.